A novel X-linked recessive form of Mendelian susceptibility to mycobaterial disease. Issue 2 (9th February 2007) - Bustamante, Jacinta; Picard, Capucine; Fieschi, Claire; Filipe-Santos, Orchidée; Feinberg, Jacqueline; Perronne, Christian; Chapgier, Ariane; de Beaucoudrey, Ludovic; Vogt, Guillaume; Sanlaville, Damien; Lemainque, Arnaud; Emile, Jean-François; et al.
Abstract : Background: Mendelian susceptibility to mycobacterial disease (MSMD) is associated with infection caused by weakly virulent mycobacteria in otherwise healthy people. Causal germline mutations in five autosomal genes ( IFNGR1, IFNGR2, STAT1, IL12RB1, IL12B ) and one X-linked ( NEMO ) gene have been described. The gene products are physiologically related, as they are involved in interleukin 12/23-dependent, interferon γ-mediated immunity. However, no genetic aetiology has yet been identified for about half the patients with MSMD. Methods: A large kindred was studied, including four male maternal relatives with recurrent mycobacterial disease, suggesting X-linked recessive inheritance. Three patients had recurrent disease caused by the bacille Calmette–Guérin vaccine, and the fourth had recurrent tuberculosis. The infections showed tropism for the peripheral lymph nodes. Results: Known autosomal and X-linked genetic aetiologies of MSMD were excluded through genetic and immunological investigations. Genetic linkage analysis of the X-chromosome identified two candidate regions, on Xp11.4–Xp21.2 and Xq25–Xq26.3, with a maximum LOD score of 2. Conclusion: A new X-linked recessive form of MSMD is reported, paving the way for the identification of a new MSMD-causing gene.